Business retention and expansion (BRE) today – research, application, and evaluation: Introduction to the special issue. Issue 2 (15th March 2017) - Darger, Michael; Barefield, Alan; Hales, Brent D.
Abstract: Business retention and expansion (BRE) has existed as a formal activity for economic development since the 1980s. BRE is one of the most prevalent activities within the field of economic development. This special issue includes research, program evaluation, and case studies demonstrating the diverse ways that economic development organizations are reaching out and responding to existing businesses. The contributed articles examine several important BRE topics. Some authors took a more theoretical approach by investigating survey data-sets from large professional associations, and others contributed practitioner stories of BRE innovations. Still others shared the results and evolution of state/provincial programs. A focused literature review was conducted by the guest editors on a set of relevant topics not covered in the contributed articles. This special issue is a collection of literature contributing to both BRE theory and practice, yet there are continuing gaps in our collective knowledge that merit future research and discussion.